Second Report on the Excavations of the Roman Fort at Richborough, Kent - Bushe-Fox, J. P. (Reports of the Research Committee of the Society of Antiquaries of London, 1928)
This is the second account of the excavations of the Roman fort at Richborough (Rutupiae), Kent, in southern England, which took place in 1924. Included are descriptions of artefacts such as pottery, coins, buildings and metalwork, together with an account of the methodology used to unearth these.